Gambaran Kualitas Air Minum Di Jabodetabek Tahun 2007-2009 - Alegantina, Sukmayati; Isnawati, Ani; Raini, Mariana (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2009)
The greater the public awareness of health can be ascertained from the number of people who determined the water used for drinking water. Water determination is one of the programs in Pharmacy and Chemistry Laboratory in Center for Biomedic and Pharmacy. Ministry of Health. Water sample is determined chemically and physically based on the parameter requirements by the Regulation of Ministry of Health (Permenkes) No 907/Menkes/SK/V11/2002. The design of the study is cross-sectional, the samples are waters from Jakarta, Depok, Tangerang, Bekasi (Jabodetabek), and outside Jabodetabek. The water samples are obtained from people who requested to determine their drinking water during period 2007- 2008. The amount of the water samples are 1668. Water determination is done both physically and chemically. Physical water determinations are including odor, TDS (total of dissolved solids), ﬂavour, temperature, turbidity, and colour. Chemical water determinations are Nitrit, Fer-rum, hardness, Chloride, Manganese, pH, Sulfate, Sulﬁde, and organic substances. Based on the results, the result shows that 27,5% of water determinations are not recommended to drink because it contained high concentration of Manganese /7,6 91), Ferrum (7,2 %), turbidity (2,4%) and colour (2,5 %). The ratio of the samples which is not recomended to drink towards total sample in one area of Tangerang is 52.0%. Based on sampling water depth >100 m, the ratio of the samples which is not recomended to drink towards the total sample that collectedfrom the depth >100 m sample is 64.2%.